New record of Lestica bibundica Leclercq, 1972 (Hymenoptera, Crabronidae) from West Africa - Hans-Joachim Jacobs (Contributions to Entomology)
A new record of Lestica bibundica Leclercq, 1972, from Togo is presented. Photos of L. bibundica, a distribution map of all species of Lestica from tropical Africa, and a determination key of females are given.